2016
DOI: 10.1016/j.ydbio.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β-catenin and p27/FOXL2 differentially regulate supporting cell proliferation in the developing ovary

Abstract: Sexual development is initiated through differentiation of testicular Sertoli cells or ovarian granulosa cells. Although these supporting cells are considered to develop from common bipotential precursors, recent evidence suggests that distinct supporting cell populations are present in the ovary, with one providing granulosa cells of the medullary follicles and the other providing granulosa cells of the cortical follicles, the latter of which support lifelong fertility. Here, we demonstrate that XX fetal gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 60 publications
5
45
0
Order By: Relevance
“…Consistent with the ability of β-catenin to inhibit testis development, GSKi also blocked the formation of laminin-delineated testis cords and the occurrence of SOX9 and AMH-positive cells in E11.5 gonads treated with FAT. However, in a related study, blocking GSK in XX foetal gonads increased supporting cell proliferation in the presence of FGF9 (Gustin et al 2016). Taken together, these observations indicate that although β-catenin blocks FAT induction of testis development, it does so by blocking growth factor induction of testis differentiation genes rather than restricting supporting cell proliferation.…”
Section: A Role For Tgfβ and Activin In Testis Organisation?mentioning
confidence: 81%
See 3 more Smart Citations
“…Consistent with the ability of β-catenin to inhibit testis development, GSKi also blocked the formation of laminin-delineated testis cords and the occurrence of SOX9 and AMH-positive cells in E11.5 gonads treated with FAT. However, in a related study, blocking GSK in XX foetal gonads increased supporting cell proliferation in the presence of FGF9 (Gustin et al 2016). Taken together, these observations indicate that although β-catenin blocks FAT induction of testis development, it does so by blocking growth factor induction of testis differentiation genes rather than restricting supporting cell proliferation.…”
Section: A Role For Tgfβ and Activin In Testis Organisation?mentioning
confidence: 81%
“…For analyses of cell proliferation in cultured gonads, EdU was added to the organ culture media at a final concentration of 20 μM for the final 2 h of culture, after which gonads were collected, dissociated into single cells and fixed with 4% PFA in PBS. Flow cytometry was carried out essentially as described , Gustin et al 2016) using cells from 0.5 to 2 gonads/sample, depending on age. For example, in vivo analysis of Sertoli cell proliferation (Fig.…”
Section: Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous studies have shown that a somatic missense mutation in the FOXL2 gene, which is expressed in the ovary, have a high correlation to granulosa cell tumors (Schmidt et al, 2004;Gustin et al, 2016). The FOXL2 mutant has also been found to affect the hormone production, apoptosis, and proliferation in vitro (Leung et al, 2016).…”
Section: Discussionmentioning
confidence: 99%